Highly efficient magnetically separable TiO2-graphene oxide supported SrFe12O19 for direct sunlight-driven photoactivity - Aziz, A.; Yau, Y.H.; Puma, G.L.; Fischer, C.; Ibrahim, S.; Pichiah, S. (Elsevier, 2014)
A highly solar photoactive, magnetically separable, TiO2-graphene oxide supported SrFe12O19 (TiO2/GO/SrFe12O19) photocatalyst was synthesised via the solid reaction of silica (SiO2)-coated SrFe12O19 with TiO2 and GO, which were produced by a hydrothermal reaction and Hummer's method, respectively. Several aspects of the material chemistry of the prepared photocatalyst were explored: its crystallite phase, particle size, surface morphology, inorganic elemental composition, adsorption-desorption hysteresis, BET surface area, organic functional group, chemical state of surface, magnetic hysteresis, coercivity (Hci), saturation magnetisation (Ms), remanence (Mr), thermal property and visible light absorption analysis. The synthesised TiO2/GO/SrFe12O19 exhibited greater ferromagnetic properties (Hci: 2103 Oe; Ms: 3.406E-3emug-1; Mr: 1.642E-3emug-1), which further enhanced its re-usability. The incorporation of GO and SrFe12O19 resulted in a drastic reduction in the bandgap energy (1.80eV). Moreover, this incorporation contributed for the higher visible light absorption. The photoactivity of TiO2/GO/SrFe12O19 was evaluated under direct sunlight for the degradation of 2,4-dichlorophenol (2,4-DCP). The degradation over a period of 5h suggested excellent photoactivity. Â© 2013 Elsevier B.V.